Sedimentary pyrite in carbonaceous shales of the Mamfe Cretaceous basin, SW Cameroon: Morphologies, composition, pyrite framboid size frequency distribution, and formation pathways. (April 2022) - Eyong, John Takem; Gabriel, Ngueutchoua; Olive, Mbesse Cecile; Jacqueline, Ntsama Atangana; Moise, Bessong; Wignall, Paul; Best, Jim
Abstract: Sedimentary pyrite morphologies, spatial distribution relative to their spectral compositions were studied in carbonaceous shales (Fc) of the Mamfe Cretaceous Basin (MCB) in SW Cameroon. Lithofacies analysis of Fc reveals laminated (Fcl), oolitic (Fco), marlstone (Fcm), algal mat (Fca) and pelletoidal (Fcp) pyritized microfacies. Results of petrographic, scanning electron microscope (SEM), backscattered electron imaging (BSEI) microscopic study coupled with energy dispersive atomic x-ray (EDAX) reveal micron-sized, densely packed framboidal and non-framboidal morphologies. Diameter measurement of 519 framboids exhibit a monomodal distribution with a narrow size-range of 0.50–14.0 μm and mean diameter range of 2.0–6.5 μm, accounting for 70.4–95.3% of all framboids measured. Non-framboidal morphologies include discrete euhedral, etched or zoned crystals, including core-sheath cell-like microstructures. Euhedral morphologies show a close spatial relationship with syngenetic mineral suite (calcite, microdolomite, chalcedony and evaporites). Meanwhile, degraded morphologies with moldic pores are mineralized in Zn and appear recrystallized, etched, in-filled by silica and clays or rimmed by ferroan carbonates and oxides. A three transitory pathways model suggests that morphological and compositional variations in pyrites are linked to authigenic precipitation, co-precipitation of Fe and Zn which depict sulphate reduction conditions under saline and carbonate lacustrine settings, followed by alteration processes. Pyritized core-sheath replicas in microstructures reminiscent of cells are indicative of a microbial paleoecosystem and could play an intrinsic role in biogeochemical recycling of S and Fe and the timing of fossilization which precedes the decay of microorganisms. Rimmed pyrite morphologies are potential indicators of local redox paleoenvironmental settings. Highlights: Pyrite framboids in carbonaceous shales of the MCB show a narrow size-range with mean diameters of 2.0–6.0 μm. Pyrite morphologies, size distribution and composition are indicators of paleo-anoxia, organic preservation, and relative timing of pyrite. Authegenic pyrite morphologies show a close spatial relationship with organic matter and syngenetic minerals in preference to diagenetic minerals. Transitory compositional defects in pyrite are linked to authigenic precipitation, co-precipitation, and replacement by trace metals.